External validation of the simplified Geneva risk assessment model for hospital‐associated venous thromboembolism in the Padua cohort. (16th December 2019) - Blondon, Marc; Righini, Marc; Nendaz, Mathieu; Glauser, Frédéric; Robert‐Ebadi, Helia; Prandoni, Paolo; Barbar, Sofia
Abstract: Background: The simplified Geneva risk assessment model (RAM) predicts the risk of hospitalization‐related venous thromboembolism (VTE) in medical inpatients in its developmental cohort but has not been validated. Objectives: To externally validate the simplified Geneva RAM. Patients/Methods: For this secondary analysis of a prospective cohort set in Padua, we calculated the simplified Geneva RAM for all participants. They were followed up for 90 days for the occurrence of adjudicated VTE. Thirty‐ and 90‐day risks of VTE were estimated by the Kaplan‐Meier method, and categories of risks compared with a Cox regression model adjusted for the use of thromboprophylaxis. Results: Among 1180 medical inpatients, the 90‐day risk of symptomatic VTE was 3.1%. The simplified Geneva RAM classified 56.9% as high risk (≥3 points; 90‐day risk of VTE of 5.2%) and 43.1% as low risk (<3 points; 90‐day risk of VTE of 0.4%). Compared with low‐risk participants, high‐risk participants had an 18‐fold greater risk of VTE than low‐risk participants (hazard ratio [HR] 17.9, 95% confidence interval [CI] 4.3‐74.7). A very high‐risk category (≥7 points) identified 5.3% of participants with a 9.5% probability of VTE at 90 days. Conclusions: In this external validation study, we confirm the excellent discrimination and clinically adequate calibration of the simplified Geneva RAM as a stratification tool to guide the use of thromboprophylaxis.